The prodigal - Lewis, Beverly, 1949- (Lewis, Beverly, 1949- Abram's daughters, 2004)
Leah's older sister Sadie has returned home from Ohio and is working toward reintegrating herself into the church. Leah is estatic to have her home, and she's happy to see her young siblings grow up. But part of Leah wonders, and still aches, when she thinks of the long-lost love of her life, Jonas Mast. She is very surprised and cautiousley optimistic to hear about the prospect of his return. But what long-buried secrets will his homecoming bring to the surface?